Pandangan Hamka mengenai Guru dalam Konteks Pendidikan Islam - Vivit Rizky Shofaryani; Candra Kurnia Saputra; Sifa Alfiana (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2024)
This research reviews Hamka's views on the role of teachers in the context of Islamic education. Hamka, as a well-known Islamic thinker and educator, provides an in-depth understanding of the characteristics and responsibilities of a teacher in forming a generation of faithful and moral Muslims. His thinking includes aspects such as teaching methods, morality, and commitment to students' personal development. Through a literature analysis approach, this research documents Hamka's valuable contributions and thoughts in the development of Islamic education.